Coverage Prediction of HF Wireless Network for Disaster Early Warning System in Indonesia - Wismanu Susetyo; Gamantyo Hendrantoro; Achmad Affandi (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2008)
HF Radio communication (2 – 25 MHz) is relatively low cost beyond the line-of-sight application. Andhave an alternative to satellite and tropospheric scatter communication. Using the wireless sensor array networkfor monitoring and identifying of sea, land, mountain etc which deal with activity of earthquake disaster inrelatively small area. The data collected and processed in one center node regional divisions, then using the HFwireless network build a national disaster early warning system. The important medium for HF radiocommunication is Ionosphere, which have spatially and temporally propagation characteristics, but when usedappropriate time and location a long range communication can be done.This paper focuses on coverage prediction of point to point HF radio communication, which used tocommunicate from six center node regional divisions to national main control system in Indonesia. Usingstatistical based tool communication analysis and prediction program VOACAP is yielded that the bestcommunication can be done at disaster frequency 12.6MHz almost all day long. Padang, Pontianak, Palu,Ambon, Kupang and Tembagapura is set as center node regional divisions with main control system at Surabaya,they have coverage capability when used in the disaster early warning system in Indonesia.Keyword: coverage prediction, HF radio communication, wireless sensor array.